Pengaruh Harga, Kualitas Layanan Dan Store Atmosphere Terhadap Kepuasan Pelanggan Pada Cafe And Resto Mindi Kec. Tutur - Handi, Mochammad; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2024)
AbstractÂ This study aims to analyze the effect of Price, Service Quality, and Store Atmosphere on Customer Satisfaction at Caffe and Resto Mindi Tutur. The research was conducted using a survey method of 115 respondents. The data analysis method used in this research is quantitative data analysis using multiple linear regression analysis. Data testing used is partial hypothesis testing (t test). The results showed that Price has a significant effect on Customer Satisfaction of Cafe and Resto Mindi Tutur, Service Quality has a significant effect on Customer Satisfaction of Cafe and Resto Mindi Tutur, Store Atmosphere has no significant effect on Customer Satisfaction of Cafe and Resto Mindi Tutur..Â Keywords: Price, Service Quality, Store Atmosphere, Customer Satisfaction.Â